Development of a Mobile Learning-Based Digital Flipbook for Professional Teacher Education Vocational Programs - Maknun, Johar; Wahyudin, Dinn; Rahmawati, Yulia; Maosul, Asep (Faculty of Teacher Training and Education Universitas Sebelas Maret Surakarta, 2023)
The main objectives of this research are developing Teaching Materials for the Vocational Teacher Professional Education Program Using M-Learning-Based Flip Book Maker Educational Media. In detail, the objectives of this study are to 1) analyse the need for developing teaching materials for the professional teacher education program Vocational using m-learning-based flip book maker educational media; 2) Develop teaching materials for the Vocational PPG Program using m-learning-based flip book maker educational media; 3) Implementation of PPG Vocational Program teaching materials using m-learning-based flip book maker educational media and 4) Knowing student responses to the use of Vocational PPG Program teaching materials using m-learning-based flip book maker educational media. Developing teaching materials that are technological developments is very important to increase the learning effectiveness of Vocational Professional Teacher Education. One of the efforts is Developing Teaching Materials for the Teacher Professional Education Program vocational Using M-Learning-Based Flip Book Maker Educational Media. The research results are expected to solve the learning problems faced by Vocational Professional Teacher Education in presenting learning media in the form of a flipbook maker based on mobile learning to improve the quality of the Vocational Professional Teacher Education learning process and outcomes. In this study, the development of mobile learning-based flip book maker educational media is used to facilitate the teaching and learning process and increase student motivation so that the teaching and learning process is more lively and vibrant.